VD_FINDINFO HC / 2019 / 315 vom 10. April 2019 - VD Tribunal cantonal (2019)
CONSTATATION DES FAITS, TÉMOIN, APPRÉCIATION DES PREUVES, CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF | 337 al. 1 CO, 157 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH)